Pelaksanaan Pembelajaran PAI pada Anak Berkebutuhan Khusus di SLB Muftia Rahma Tilatang Kamang - Elsa Nur'aini; Junaidi Junaidi; Januar Januar; Nurhasnah Nurhasnah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
At SLB Muftia Rahma Tilatang Kamang there are problems regarding conducting PAI learning for children with special needs,because teachers have difficulty conveying subject matter because of the diverse students, teachers who have graduated from guidance and counseling education, lack of school facilities and infrastructure, many teachers are unable attend as well as students of different levels combined in one class. The type of research used is qualitative research. The teacher as a key informant and the principal of the SLB Muftia Rahma Tilatang Kamang school as a supporting informant. Data collection techniques used are observation, interviews and documentation. The data analysis techniques used are data reduction, data display and data verification. To test the validity of the data, source triangulation and technique triangulation were used. The results showed that the implementation of PAI learning for children with special needs at SLB Muftia Rahma teachers understood the characteristics of students, mastered the subject matter by applying approaches, strategies and learning methods, developed curriculum adapted to students' conditions, prepared lesson plans and used learning media, communicated with effective, empathetic and polite as well as evaluating with questions and answers and demonstrations. The problems faced by the teacher are conveying subject matter to students, inviting students to work together and managing time for students.